THE INFLUENCE OF SERVICE QUALITY, PRICE, AND LIFESTYLE ON STUDENT PURCHASE DECISION OF SHOPEE USERS AT SAM RATULANGI UNIVERSITY - Shinta J. C. Wangke; Mandagi, Christina Nadya; S. L. H. V. Joyce Lapian (Universitas Sam Ratulangi, 2024)
Competition between e-commerce in Indonesia is very tight and dynamic, with several main players competing to get a larger market share, one of which is Shopee. This study explores the Influence of Service Quality, Price, and Lifestyle on Purchase Decisions of Shopee users at Sam Ratulangi University. The backdrop of the study is the rapid technological development that has significantly impacted various aspects of daily life, including shopping behaviors. This study employs quantitative analysis, using statistical methods to examine the relationships between the independent variables (service quality, price, and lifestyle) and the dependent variable (purchase decision). The research focuses on how e-commerce platforms like Shopee, influence consumer behavior and purchase decisions. Shopee is noted for its attention to service quality, price, and lifestyle to attract and retain customers. The intense competition among marketplaces, with varying price strategies, service quality, and promotions, is also a key factor in the study. Keywords: Service Quality, Price, Lifestyle, Purchase Decision